Amola rock glacier, Val d’Amola, Italian Alps - Seppi R.; Baroni C.; Dall’Amico M.; Rigon R.; Zampedri G.; Zumiani M.; CARTON, ALBERTO (country:CHE, 2011)
Topographic measurements are in progress since 2001 on a glacierderived, active rock glacier (named Amolarock glacier, acronym AmRG, coordinates: 46° 12’ 09” N, 10° 42’ 46” E) located in the AdamelloPresanella group, Central Italian Alps. In addition, data on the ground temperature measured few centimetres below the surface are available since 2004. The displacement data show that some areas of the rock glacier currently (20012009) move with velocities ranging from 10 to 20 cm/year, while other sectors can be defined as “dynamically inactive”. The average velocity is significantly variable from year to year, ranging from a minimum of 0.06 m/year (2007 2008) to a maximum of 0.13 m/year (20062007), and a slowing trend has been recorded in the last two years. In 20062007 a higher rate of displacement seems to be related to a rise in the mean air temperature that probably caused a corresponding rise in the ground temperature. However, in the last year of measurements (20082009), an increase in the ground temperature caused by the large amount of snow of the preceding winter, did not result in a corresponding increase of the displacement rate. The dynamic behaviour of this rock glacier reacts very fast to the external forcing, and its response seems to be modulated by the amount and evolution of the snow during winter, due to its effect on the ground temperature. Thus, not only the temperature but also the projected changes in the amount and distribution of precipitation, especially as snow, should be taken into account in assessing the response of this landform to future climate change.